Penggunaan Bahasa Persuasi dan Elemen Bahasa pada Iklan Makanan di YouTube - Rahma Sari (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to identify the use of persuasive language and language elements in food advertisements on the YouTube platform. Food advertising on digital media is an effective means of attracting consumer attention. With a qualitative descriptive approach, this research reveals various persuasion language techniques, such as the use of invitations and suggestions such as "try", "again", "really", and "interesting", which encourage the audience to try the product. In addition, repetition of sentences and use of hyperbole to highlight product advantages were found to be effective in attracting attention and increasing consumer interest. The results of this research indicate that persuasive language in food advertising plays an important role in generating interest and encouraging consumers to buy products. These findings provide insight into language-based marketing strategies that can be used to influence consumer decisions.